Adenocarcinoma at Anastomotic Site of Ureterosigmoidostomy Potentially of Urothelial Origin Spreading to the Upper Urinary Tract - Katsuhiro Makino; Haruki Kume; Teppei Morikawa; Aya Niimi; Tetsuya Fujimura; Tohru Nakagawa; Hiroshi Fukuhara; Yukio Homma (Case Reports in Urology)
Ureterosigmoidostomy is associated with the risk of several late complications including cancer development at anastomotic sites. We present an unusual case with adenocarcinoma of the anastomotic site associated with multiple adenocarcinoma lesions in the upper urinary tract. A 69-year-old man complained of persistent melena and hematuria. He had undergone radical cystectomy for high-grade bladder cancer and ureterosigmoidostomy 30 years before. Colonoscopy showed a tumor at the right ureterocolonic anastomosis, which was endoscopically resected and histologically diagnosed as adenocarcinoma. Seven years later, a tumor of the left ureterocolonic anastomosis associated with hydronephrosis was found. He underwent temporal percutaneous nephrostomy followed by sigmoidectomy and left ureterocutaneostomy. Eighteen months after the operation, computed tomography (CT) detected left renal pelvic tumor with a mass along the former nephrostomy tract. Left nephroureterectomy and resection of the nephrostomy tract tumor revealed adenocarcinoma with multiple lesions of adenocarcinoma in the ureter. These tumors showed atypical immunohistochemistry as a colonic adenocarcinoma: positive for cytokeratin 7, negative for cytokeratin 20, and negative for β-catenin nuclear accumulation. Anastomotic site adenocarcinoma of the present case is potentially of urothelial origin because of unusual clinical manifestation and immunohistochemistry as a colon cancer.